2023
DOI: 10.1371/journal.pone.0280031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory presentation of first-time antenatal care visits of pregnant women in Ghana, a hospital-based study

Abstract: Background The WHO recommends pregnant women attend antenatal clinic at least three times during pregnancy; during the first, second and third trimesters. During these visits, an array of clinical and laboratory tests is conducted. The information obtained plays an important role not only in the management and care of pregnancy, but also guides policies targeted at addressing pregnancy-induced health challenges. This study therefore presents laboratory and clinical information of pregnant women at their first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, access to screening for infections like HIV serves as a facilitator for preventive measures and timely diagnosis. A study conducted in Ghana in 2018 confirmed that the prevalence of HIV among pregnant women was lower compared to the general population [ 24 ]. On the other hand, the testing policy during prenatal care has certain effects on the male population, as women discover the presence of HIV infection during pregnancy or through illness, leading to this diagnosis being discovered by their male partners [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, access to screening for infections like HIV serves as a facilitator for preventive measures and timely diagnosis. A study conducted in Ghana in 2018 confirmed that the prevalence of HIV among pregnant women was lower compared to the general population [ 24 ]. On the other hand, the testing policy during prenatal care has certain effects on the male population, as women discover the presence of HIV infection during pregnancy or through illness, leading to this diagnosis being discovered by their male partners [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It means they are more likely to not allow adequate distance between their pregnancies, which may predispose them to iron de ciency anemia [16]. Abuku, Allotey, and Akonde [17] state that pregnant women should monitor their hemoglobin levels at every ANC visit. However, this study found that half of the respondents did not monitor their Hb at regular intervals.…”
Section: Practices Of Iron De Ciency Anemia In Pregnancymentioning
confidence: 99%
“…33 Malaria parasitaemia in pregnancy prevalence of 2.4%-28.8%, over 2016-2019, have been reported in the near-by South Tongu, Central Tongu and Akatsi districts. [34][35][36]…”
Section: Study Design Area Populationmentioning
confidence: 99%